Attitudes May Be Hard to Change: Canadian Organ Donors Consider Face and Hand Donation. Issue 11 (29th November 2021) - Lafreniere, Ann-Sophie; Al-Halabi, Becher; Thibaudeau, Stephanie; Temple-Oberle, Claire
Abstract : Objective: Despite the success of composite tissue allograft (CTA) such as face and hand transplant at improving recipients' quality of life, organ donors' hesitation needs to be better understood. The aim of the study was to assess Canadian organ donors' willingness to donate their face and hands, and the efficacy of an educational intervention. Methods: Canadians registered for organ donation were invited to complete an online survey about CTA. An interactive vignette was introduced part way through to clarify transplant-related concepts, with repeat of questions post-vignette exposure to assess attitudes pliability. Results: A total of 942 participants completed the survey. Fifty-two percent of donors were willing to donate their face after passing, whereas 80% were willing to donate their hands. Reasons to refuse CTA donation included the risk of upsetting their family, having someone look like them, and wanting their body to remain intact. Donors' willingness to donate their face (38%, P < 0.001) and hands (79%, P = 0.67) decreased following vignette exposure. Comparative analysis of our interventional vignette with a similar study where donors' donation readiness increased after an educational intervention revealed that our vignette lacked a strong enough emotional component to positively impact donors' attitude to CTA, and may have exposed participants to alternatives to transplant they were not previously aware of. Conclusions: Canadian organ donors surveyed were willing to donate their face and hands following death, a willingness reduced after watching our informative vignette. Further qualitative work is required to better understand the educational needs and areas to address to increase donors' acceptance of CTA.